Comparison of Efficacy, Safety, and Humanistic Outcomes of Iron-Chelation Therapy in Pediatrics Suffering from Transfusion-Dependent β-Thalassemia Major - Narayana Goruntla; P. Stephen Azarya; Mahitha Chalagundla; Dasaratha Ramaiah Jinka; Pradeepkumar Bhupalam; Vishnuvandana Bandaru (Indian Journal of Medical Specialities)
Introduction: Beta-thalassemia major (β-TM) is a severe form of genetic disorder that affects the patient's quality of life. Iron-chelation therapy (ICT) is recommended in these patients to reduce the complications (iron overload) associated with repeated blood transfusion. Objective: The present study aims to compare the efficacy, safety, and Pediatric Quality of Life (PedsQL) of the single and combinational ICT regimens in β-TM. Materials and Methods: This prospective, comparative study was conducted in the outpatient department of a daycare pediatric hospital located in South India. Patients diagnosed with β-TM, ages between 2 and 12 years, under ICT regimens were recruited. A suitable data collection form and PedsQL questionnaire was used to obtain demographics, blood transfusion, serum ferritin, hematological, biochemical, and PedsQL data of the study participants. One-way ANOVA and Chi-square test were used to compare the safety, efficacy, and PedsQL. Results: A total of 97 participants who met the study criteria were enrolled in the study and divided into three groups: Group I (n = 45) Deferasirox alone, Group II (n = 28) Deferasirox + Deferiprone, and Group III (n = 24) deferasirox + deferoxamine. The mean difference of ferritin concentration in Group III (695.3 ± 1252.4) was high compared to Group I (91.31 ± 702.6) and Group II (392.5 ± 1083.5) regimens with a P = 0.0053. In Group III, a significant reduction in physical and school functioning was observed. Conclusion: Oral Deferasirox combined with subcutaneous deferoxamine shows a great significant reduction in ferritin levels, but this combination is associated with a significant rise in hepatic enzymes, and poor physical and school functioning. An oral Deferasirox combined with oral Deferiprone is a safe and effective regimen in the treatment of β-TM, without affecting any domain of the Health-Related Quality of Life.